PERLINDUNGAN PEKERJA PEREMPUAN MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (Studi Pada Spbu Galangan Kapal Kota Makassar) - Nur Aslamia Amin; Andi Kasmawati; Imam Suyitno (Jurnal Tomalebbi, 2019)
Abstract. This study aims, (1) To find out the fulfillment of the rights of women workers who work at the Makassar City Shipyard Gas Stations (2) To find out the procedures for the protection of women workers at the Makassar Shipyard Gas Stations are in accordance with Law Number 13 of 2003 concerning Manpower. (3) To find out the factors that determine the implementation of the protection of women workers at the Makassar City Shipyard Gas Station. This type of research is descriptive research and uses a qualitative research approach. The data sources used are primary data and secondary data. The primary data are 1 operational manager of shipyard gas stations and 7 female operators at shipyard gas stations. While secondary data are laws, books, journals, papers, and materials from the internet. Data collection techniques include: Observation, Interview and Documentation. Data analysis used in this qualitative research is data reduction, data display and decision making or verification. Based on the results of the study, namely: (1) the fulfillment of the rights of female workers has been fulfilled which includes the right to menstrual leave, the right to maternity leave, the right to miscarriage leave, the right to maternity leave, the provision of working time, and overtime time (2) the protection of female workers is also quite fulfilled in social aspects, technical aspects (occupational safety), occupational health aspects, but in the aspect of worker welfare still need optimization (3) the determining factor for the fulfillment of the protection of women workers is the harmony between the company and the women workers themselves.